2022
DOI: 10.3389/fpls.2022.979348
|View full text |Cite
|
Sign up to set email alerts
|

APETALA2/ethylene responsive factor in fruit ripening: Roles, interactions and expression regulation

Abstract: Insects and animals are attracted to, and feed on ripe fruit, thereby promoting seed dispersal. As a vital vitamin and nutrient source, fruit make up an indispensable and enjoyable component of the human diet. Fruit ripening involves a series of physiological and biochemical changes in, among others, pigmentation, chlorophyll (Chl) degradation, texture, sugar accumulation, and flavor. Growing evidence indicates that the coordinated and ordered trait changes during fruit ripening depend on a complex regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 133 publications
0
9
0
Order By: Relevance
“…AP2/ERF, a large family of transcription factors with multiple functions, holds a pivotal role in plant growth, hormone regulation and response to environmental stresses [28]. In recent years, there has been increasing evidence that these TFs are also key regulators of fruit quality attributes such as ripening, color, texture, and avor [29,30]. Studies have shown that the transcriptome and expression pro le analysis of ERF gene family showed that it plays the role of transcriptional activator and suppressor in durian fruit ripening process [31].…”
Section: Introductionmentioning
confidence: 99%
“…AP2/ERF, a large family of transcription factors with multiple functions, holds a pivotal role in plant growth, hormone regulation and response to environmental stresses [28]. In recent years, there has been increasing evidence that these TFs are also key regulators of fruit quality attributes such as ripening, color, texture, and avor [29,30]. Studies have shown that the transcriptome and expression pro le analysis of ERF gene family showed that it plays the role of transcriptional activator and suppressor in durian fruit ripening process [31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that photosynthesis biosynthetic pathway might be the one of major target by ET-mediated ripening process. In a consistency, previous studies reported that ET signaling factors like APETALA2/ethylene responsive factor (AP2/ERF) family genes play an important role in the fruit ripening through regulation of genes related to photosynthesis, chlorophyll metabolism during fruit ripening ( Zhai et al., 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…The first, TraesCS7D01G148000, is hypothesized to encode a protein linked to aging processes in wheat, crucial for grain yield as they potentially facilitate nutrient reallocation to developing seeds [ 73 ]. The second, TraesCS7D01G117600, is believed to encode an ethylene-responsive transcription factor (ERF), part of the AP2/ERF family, instrumental in stress response, reproduction, defense, and hormone secretion regulation [ 74 ], with implications for flower development control [ 75 ]. The third, TraesCS7D01G117100, might be associated with histone H3, playing a role in the vernalization-induced transition from vegetative to reproductive growth through histone methylation [ 50 , 51 ], suggesting its potential impact on GNS due to the established relationship between GNS and growth phases [ 76 ].…”
Section: Discussionmentioning
confidence: 99%